SVF Therapy of Delayed Fracture Union in Patients with Multiple Combat Injury. Case Report - Maslennikov, S. O.; Kozhemyaka, M. O.; Golovakha, M. L.; Масленніков, Сергій Олегович; Кожем'яка, Максим Олександрович; Головаха, Максим Леонідович (My University, 2024)
Delayed union of fractures is one of the most frequent complications in orthopedic practice, especially in polytrauma patients. With the development of new methods of regenerative medicine, including the use of adipose derived stromal cells as a component of the stromal-vascular fraction (SVF), new possibilities for conservative treatment of this problem have emerged. This article presents a clinical case of conservative treatment of delayed union of a radial bone fracture using local SVF injections. In the fracture space, SVF with PRP creates a pool of cells that could differentiate towards surrounding tissue, releases various inducers of tissue growth and, via an indirect chemotactic effect on receptors, mobilizes the body’s own resources and creates conditions for angiogenesis and trophism in the injured segment. In the patient with delayed consolidation after SFV-therapy, progress in clinical and radiological dynamics was noted with complete healing within 7 months. The positive clinical result provides a basis for further study and implementation in practice.
Keywords: radial fractures; stromal-vascular fraction; osteosynthesis; adipose derived stromal cells